Causation in competition law damages actions / Claudio Lombardi, KIMEP University. - Lombardi, Claudio, 1983- (Global competition law and economics policy., 2020)
Competition law damages actions are often characterized by the uncertainty of the causal connection between the infringement and the harm. The damage consists in a pure economic loss flowing from an anticompetitive conduct. In such cases, the complexity of the markets structures, combined with the interdependence of individuals' assets, fuel this causal uncertainty. In this work, Claudio Lombardi elucidates the concept of causation in competition law damages actions and outlines its practical implications in competition litigation through the comparative analysis of the relevant statutory and case law, primarily in the European Union. This book should be read by practitioners, scholars, and graduate students with experience in competition law, as well as those interested in analyzing economic torts and causation in general.